STUDI PENDAHULUAN KEANEKARAGAMAN PAKU DI HUTAN KOTA LINARA, METRO-LAMPUNG - Saniah, Nikmatus; Ummah, Allydya C.; Anggita, Anggita; Fauziah, Firza; Wakhidah, Anisatu Z. (BIOLOVA, 2025)
: Urban forest is a plant vegetation in urban areas that provides maximum environmental benefits such as, protection, aesthetics, recreation, and other specific uses. Linara City Forest is one of the urban forests in Metro City. Surveys of fern diversity have never been carried out in this area. Ferns are plants that can live in a variety of environments, both terrestrial, epiphytic and aquatic. This study aimed to conduct an initial survey of the diversity of species, number, and the ecological role of ferns in the Linara City Forest. The data collected by used exploratory method with random sampling points. The data collected was then analyzed qualitatively. The results of this preliminary study showed that there were 8 species of ferns, Pyrrosia pilloselloides, Adiantum trapeziforme, Platyercium bifurcatum, Lygodium palmatum, Pnemuatopteris pennigera, Nephrolepis cordifolia, Gymnocarpium dynopteris, Adiantum raddianum. The most common fern species found in Linara City forest in this study was Pneumatopteris pennigera (117 individuals). Ecologically, ferns function as litter mixters for the formation of soil nutrients, producers in the food chain, habitat for some animals, especially insects, protect the soil from erosion and can maintain soil moisture.